Emotions in Performance: Between Rape and Research Lab - Neuerburg-Denzer, Ursula (InTensions, 2008)
Framed by the narrative of staging and performing a rape, this paper will map the subjective journey of six student research practitioners at a university’s Emotion Lab. The student performers explored their affective bodies through breath and voice as well as conventionalized, realistic and expressive gesture. A series of questions that arose in this context circled around themes such as “awareness,” “contagion,” “fear,” “control,” “containment” and “spillage.” This lead to an investigation of the emotions surrounding (the performed) emotions, for example: “fear.” “Are there emotions you are afraid to express?” “Are you afraid an emotion can overwhelm you?” The immediate relevance of these investigations becomes imminent when undergraduate acting students are asked to perform scenes that deal with emotional extremes: such as staging a rape scene.